Students’ Learning Interest during Online Biology Course: A Correlation Study - Hasan, Ani Mustapa; Anwar, Lutfiyah Fadhilah; Baderan, Dewi Wahyuni Kiyai (FKIP Universitas Lampung, 2022)
The objective of this study is to know the correlation between online learning and students’ learning interest on biology course. This study is a correlational quantitative research. The sampling technique is purposive sample with a total sample of 164 students. The technique employed for data collection is preliminary observation, interview, and questionnaire. The data analysis technique employed used are descriptive statistical data, data normality test, linearity test and Pearson product moment correlation test. The result of this study revealed that there is a significantly positive correlation between the online learning and students’ learning interest on Biology course with correlation coefficient (r) = 0.675 which was considered as strong correlation at level of 0.5% with the score of tcount > ttable = 11.671 > 1.654 in other words, the better the implementation of online learning, the better the students’ learning interest on Biology Course. Teachers’ innovation in online learning can support students learning interests because learning interests are not permanent so teachers must have the ability to create interesting online learning. Keywords: online learning, students’ learning interest, biology. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp529-539